2009
DOI: 10.1111/j.1440-1746.2009.05870.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat to produce non‐alcoholic fatty liver in the rat

Abstract: Extending the feeding period of the high fat/ad lib diet for 5 weeks placed our rats with Type I to II NAFLD compared to the more progressed Type III state previously obtained after 3 weeks feeding. The milder condition obtained raised the prospect of genetic modifiers present in our rats that resist disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
4
24
1
1
Order By: Relevance
“…Depending on acute or chronic pathophysiological conditions, the UPR transducer IRE1α may act as an RNase or a scaffold through its cytosolic domain to modulate inflammatory and/or metabolic stress signaling pathways (8, 15). It was previously reported that the IRE1α-XBP1 pathway was activated in the livers of NASH patients or animal models (3234). However, our study showed that a HFD de-activated IRE1α RNase activity towards both Xbp1 mRNA splicing and select miRNA processing in the liver.…”
Section: Discussionmentioning
confidence: 96%
“…Depending on acute or chronic pathophysiological conditions, the UPR transducer IRE1α may act as an RNase or a scaffold through its cytosolic domain to modulate inflammatory and/or metabolic stress signaling pathways (8, 15). It was previously reported that the IRE1α-XBP1 pathway was activated in the livers of NASH patients or animal models (3234). However, our study showed that a HFD de-activated IRE1α RNase activity towards both Xbp1 mRNA splicing and select miRNA processing in the liver.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, animals of HA and HL groups could be considered obese since their final body weight was 30 % more than that of either of the other groups, with a body increase significantly higher. In addition, in this study, we chose a nutritional model that has been used previously by other authors [26,27] in which the H diet leads to steatosis, which can be confirmed by plasma levels of ALT and AST, presence of dyslipidemia (Table 3), liver histological examination (Fig. 1) and assessment of total liver fat (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…6 One of the important features of NAFLD is abnormal liver function and nonalcoholic steatosis. 7 Although the pathogenic process of NAFLD is unclear NAFLD has been linked with obesity. Therefore, many chemical agents are used as lipid-lowering medication.…”
Section: Introductionmentioning
confidence: 99%